Anaerobic co-digestion of pig manure and algae: Impact of intracellular algal products recovery on co-digestion performance. (April 2015) - Astals, S.; Musenze, R.S.; Bai, X.; Tannock, S.; Tait, S.; Pratt, S.; Jensen, P.D.
Graphical abstract: Highlights: Pig manure was anaerobically co-digested with raw and processed algae. Processing increased algae biodegradability but not its degradation rate. Synergy between raw algae and pig manure increased methane yield of the mixture. There was no significant synergy between processed algae and pig manure. Concept was presented for a combined biorefinery processing pig manure and algae. Abstract: This paper investigates anaerobic co-digestion of pig manure and algae ( Scenedesmus sp.) with and without extraction of intracellular algal co-products, with views towards the development of a biorefinery concept for lipid, protein and/or biogas production. Protein and/or lipids were extracted from Scenedesmus sp. using free nitrous acid pre-treatments and solvent-based Soxhlet extraction, respectively. Processing increased algae methane yield between 29% and 37% compared to raw algae (VS basis), but reduced the amount of algae available for digestion. Co-digestion experiments showed a synergy between pig manure and raw algae that increased raw algae methane yield from 0.163 to 0.245 m 3 CH4 kg −1 VS. No such synergy was observed when algal residues were co-digested with pig manure. Finally, experimental results were used to develop a high-level concept for an integrated biorefinery processing pig manure and onsite cultivated algae, evaluating methane production and co-product recovery per mass of pig manure entering the refinery.